Communication Aspect of National Testing Digitalization: Investigating Key Stakeholders’ Satisfaction - Miloš Jevtić; Slavica Cicvarić Kostić; Milan Okanović (Management)
Research Question: The paper deals with the analysis of the elements of the communication system in the process of digitalization of the national testing process in the Republic of Serbia. Motivation: National testing represents an important segment of education in most countries. Considering that it involves a large number of stakeholders and activities, innovations based on the implementation of new technologies are complex and require significant efforts and resources for their implementation. The digitalization of national testing in Serbia, in addition to the development of software and organizational solutions, is accompanied by the development and implementation of a communication system aimed at facilitating the acceptance of innovations by all participants. This paper addresses the analysis of the efficiency of the elements of the communication system and satisfaction of stakeholders with them, at the final exam at the end of primary education in the Republic of Serbia. Idea: The paper aims to describe a successful communication system implemented to support the process of national testing digitalization. Effective communication is essential due to the large number of participants involved in the process and should ensure national testing effectiveness and transparency. Data: For the analysis of the satisfaction of two stakeholder groups with the highest interest and influence in the process of conducting the final exam, data obtained from surveys conducted in 2021, 2022, and 2023 were used. Each year, the questionnaire was completed by over 900 primary school principals and over 8,000 parents of final-grade pupils. Tools: In the research, a questionnaire specifically designed for two stakeholder groups - primary school principals and parents of final-grade pupils was used. Statistical analysis was performed using SPSS software. Descriptive statistics and correlation analysis were employed. Findings: The research has found that high satisfaction among key stakeholders (primary school principals and parents) is achieved through a carefully designed and implemented communication system, which includes an internet portal, written and video instructions, as well as direct support from trained and expert individuals. The communication system element that has the greatest impact on principals' satisfaction is the administrative portal, while for parents, it comprises all instructions prepared for carrying out activities. Contribution: This paper expands on existing research related to the digitalization of national testing and highlights the key elements of the communication system to enhance participant satisfaction in the process.